Population fluctuation of Spodoptera frugiperda eggs and natural parasitism by Trichogramma in maize - doi: 10.4025/actasciagron.v35i3.16769 - Sônia Thereza Bastos Dequech; Cátia Camera; Vinicius Soares Sturza; Leandro do Prado Ribeiro; Ranyse Barbosa Querino; Sônia Poncio (Acta Scientiarum: Agronomy, 2013)
This study aimed to evaluate the fluctuation of S. frugiperda eggs and natural parasitism by Trichogramma and identify and quantify parasitoid species in maize fields in the state of Rio Grande do Sul, Brazil. Surveys were carried out in two growing seasons: in 2006/2007 we assessed one growing season (late sowing) in Santa Maria, and in 2007/2008 we assessed two growing seasons (early and late sowing) in Santa Bárbara do Sul. Daily air temperature and rainfall were recorded at both locations. In each evaluation, entire plants were examined for the presence or absence of S. frugiperda egg masses, which were analyzed for larvae hatching or parasitoid emergence. The number of S. frugiperda eggs is higher between 8 and 30 days after plant emergence, decreasing in the later stages of maize growth; the occurrence of parasitoids begins about two days after pest egg occurrence; S. frugiperda egg parasitism is low; and eggs are parasitized by Trichogramma pretiosum and Trichogramma atopovirilia, with marked predominance of the first and possible occurrence of both parasitoid species in the same egg mass.